2017
DOI: 10.1016/j.neubiorev.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-motor dual-task interference: A systematic review of neural correlates

Abstract: Cognitive-motor interference refers to dual-tasking (DT) interference (DTi) occurring when the simultaneous performance of a cognitive and a motor task leads to a percentage change in one or both tasks. Several theories exist to explain DTi in humans: the capacity-sharing, the bottleneck and the cross-talk theories. Numerous studies investigating whether a specific brain locus is associated with cognitive-motor DTi have been conducted, but not systematically reviewed. We aimed to review the evidences on brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(195 citation statements)
references
References 51 publications
8
184
1
2
Order By: Relevance
“…In general, several models have tried to explain dual tasks and their effects in humans. However, there is no consensus on which theory best predicts the effects of DT [47,110]. The most widely accepted theories are summarized below ( [40,54,95] postulates that cognitive-motor interference is caused by a limited-capacity parallel processor that divides resources among to-be-performed tasks.…”
Section: Dual-task Theoriesmentioning
confidence: 99%
“…In general, several models have tried to explain dual tasks and their effects in humans. However, there is no consensus on which theory best predicts the effects of DT [47,110]. The most widely accepted theories are summarized below ( [40,54,95] postulates that cognitive-motor interference is caused by a limited-capacity parallel processor that divides resources among to-be-performed tasks.…”
Section: Dual-task Theoriesmentioning
confidence: 99%
“…Irrespective of the cognitive task modality, during CMI, a performance deterioration is usually observed in the cognitive and/or in the motor task (Leone et al, 2017). Focusing on the motor behavior, studies on dual-task walking demonstrated alterations in gait velocity, stride length and stride time (Beurskens et al, 2016;De Sanctis et al, 2014;Malcolm et al, 2015;Patel et al, 2014;Pizzamiglio et al, 2017;Plummer et al, 2015).…”
Section: Performance Perturbation Under CMImentioning
confidence: 99%
“…However, it appears that dorsolateral prefrontal cortex, a brain region responsible for higher-level task 762 executive, is bringing several deficits together, since it is: 1) structurally degraded with aging), 2) likely 763 responsible for reduced explicit adaptation , 3) likely involved in dual-task 764 execution (Leone et al, 2017;Watanabe and Funahashi, 2018), and 4) important for working memory 765 capacity . This brain region appears to be an interesting target when 766 designing future studies that investigate the cause for explicit strategy decline with aging.…”
Section: Explicit Adaptationmentioning
confidence: 99%